Fingerprint of persistent organic pollutants in tissues of Antarctic notothenioid fish specimens - Lana, Nerina Belén; Berton, P.; Covaci, Adrián; Ciocco, Nestor Fernando; Barrera Oro, Esteban; Atencio, Adrian Gonzalo; Altamirano, Jorgelina Cecilia (Science of The Total Environment)
In the present work, persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT) and metabolites, polybrominated diphenyl ethers (PBDEs), and hexachlorocyclohexane (HCH) were analyzed in three Antarctic notothenioids fish species: Trematomus newnesi (TRN), Notothenia coriiceps (NOC) and Notothenia rossii (NOR). The contribution of each POP-family to the total load was as follows: PCB (40%) >DDT (27%) >PBDEs (23%) >HCH (10%). Among the 23 PCB congeners analyzed, penta-CBs homologues were the prevalent group, followed by hexa-CBs and hepta-CBs. DDT and its metabolites presented the following trend: p,p?-DDT >p,p?-DDE ~ p,p?-DDD. PBDE profile was dominated by BDE-47 and BDE-99 congeners, followed by BDE-100 > BDE-28 > BDE-154, BDE-153. Among HCHs, the γ-HCH isomer was detected in all samples, constituting 69% total HCH load, while α-HCH and β-HCH contributions were 15% and 16%, respectively. The levels of POPs reported here suggest that NOR and NOC are more susceptible to accumulate the analyzed contaminants than TRN, a specie not previously not analyzed for POPs. Distribution of POPs among different tissues of the three species (muscle, liver, gonads, and gills) was also investigated. Considering lipid weight, the general pattern of POPs distribution in tissues indicated that while gonads showed higher levels of PCBs, DDTs and HCH, the most significant PBDE concentrations were recorded in gills. Also, a comparative analysis of POPs concentration in fish samples from Antarctic area was included. Fil: Lana, Nerina Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Berton, P. Consejo Nacional de ...